PERAN GURU DALAM SIKAP SOSIAL PESERTA DIDIK PADA PEMBELAJARAN TEMATIK BERMUATAN ILMU PENGETAHUAN SOSIAL KELAS IV SDN PENDEMSARI SLEMAN - Fauziah, Dwi Septy Maysaroh; Zulfiati2, Heri Maria (Universitas Sarjanawiyata Tamansiswa, 2020)
This research intended to describes the teacher role in the developing social attitude of a student in thematic learning that contains social sciences with fourth-grade SDN Pendemsari Sleman. The method used in this research is qualitative descriptive. The Source of data in this research is primary and secondary data sources. The primary data resource in this research is the teachers, the headmaster, and the student of fourth-grade SDN Pendemsari Sleman. Data analysis techniques in this research through the steps of data collection, data reduction, data display, and conclusion drawing. Results of research on the teacher role in the developing social attitude of a student in thematic learning contain social sciences with fourth-grade SDN Pendemsari Sleman indicate the fourth-grade teachers have developed social attitudes of student fourth-grade with efford became a countershaft, enforces, evaluator, motivator and provide a good example about social attitudes, establish a group at social sciences learning to practice cooperation, citing as an example of student for a good social attitude and the obstacle factor in developing social attitudes is the outside school environment like a bad family environment nor a friend of the sam age environment, and the time-consuming conditioning.